Preparation and detrmination of many of transitional metals complexes containing new ligands of thiourea derivatives - Luma Mubarek (College of Education for Pure Sciences, 2006)
A new complexes of Co(II), Ni(Il), Cu(II) and Zn(II) are synthesized with new bidentate ligand l-(6-nitro-2-pyridyI)-3-ethylenethiourea) (npe) and in some cases mixed with (2,2' biperidyl) (Li) and (4-methyiperidyl) (L2) as bi and monodentate ligands. These complexes have been characterized by means of micro analysis (N&M), molar conductance measurements, magnetic measurements I.R, and electronic spectral studies.